Police equilibrium: a glocal assessment of the demand and supply of police - Dau, Philipp M. (Policing and society, 2023)
Police resources are scarce public goods and have to be used with maximum efficiency. One dimension of efficiency is the spatial and temporal alignment of police presence to calls-for-service. The research question of interest in this paper is whether the police are where and when they are needed most. We employ a supply and demand model based on police presence and the occurrence of calls for police service. We use GPS data from 100 tracked police vehicles and data on calls-for-service from a mid-sized European police agency. We find that most segments receive relatively more police presence than calls-for-service alone would warrant and that calls-for-service as well as emergency calls show little spatiotemporal variation. Further, police presence is found to be the main driver in changes regarding police provision across streets. We discuss the need to develop more evidence-based frameworks to investigate the effectiveness of police patrol and response deployment. The insights can assist police chiefs to identify streets with high demand for police services and to understand the predictability of police demand within their jurisdiction.